2014
DOI: 10.1002/2327-6924.12051
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia decision support intervention: A promising approach to enhance the intention to complete an advance directive among hospitalized adults

Abstract: Purpose We examined the acceptability and initial efficacy of a multimedia decision support (MDS) intervention to improve intention to complete an advanced directive (AD) among hospitalized adults following an episode of critical illness. Data sources We used comparative quasi‐experimental posttest only design. Forty‐nine hospitalized adults, recovering from a critical illness, received either MDS or AD educational brochure. Demographic characteristics and self‐report measures of AD knowledge were captured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Seven pilot trials tested ACP tools for future decisions, 15,2327,34 and 14 tested tools to support patient engagement in current decisions. 7,1622,2833 Seven of the pilot trials 1519,21,22 have been followed by published RCTs, 3542 and a search of trial registries revealed that 2 additional studies 7,20 are being tested in clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Seven pilot trials tested ACP tools for future decisions, 15,2327,34 and 14 tested tools to support patient engagement in current decisions. 7,1622,2833 Seven of the pilot trials 1519,21,22 have been followed by published RCTs, 3542 and a search of trial registries revealed that 2 additional studies 7,20 are being tested in clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Hickman and colleagues created a multimedia decision support intervention that delivers education about advanced directives to patients recovering from critical illness (Hickman, Lipson, Pinto, & Pignatiello, 2013). Brought to the bedside via laptop computer, this intervention increased the intent to sign an advanced directive by 25 times compared to the commonly used advanced directive educational brochure, “Putting it in writing”.…”
Section: Providing Decision Support Interventionsmentioning
confidence: 99%
“…3 Prior research has found that the end-of-life care preferences of patients hospitalized with HF change over time 4 and after hospitalizations, 5 likely as a result of their hospital ex-perience. 5,6 Exposure to life-sustaining treatments during hospitalization provides patients with the experience necessary to help contextualize their advance care planning (ACP) choices and may provide a timely opportunity to educate patients about ACP before discharge. 7 Research supports the promise of multimedia decision aids for ACP.…”
Section: Introductionmentioning
confidence: 99%
“…7 Research supports the promise of multimedia decision aids for ACP. 6,8,9,10 In this study at two academic medical centers we explored the feasibility of a brief educational video tool combined with a hospital-based health educator in initiating ACP dialogue aimed at improving completion rates of advance directive (AD) and physician orders for life sustaining treatment (POLST) forms.…”
Section: Introductionmentioning
confidence: 99%